Influence of virtual reality on the process of personality socialization: A distance model of socialization - Zhaparova, Baglan; Kolyeva, Natalya; Akhmuldinova, Aigul; Shnaider, Fatima; Mambetalina, Aliya (International Journal of Innovative Research and Scientific Studies, 2023)
The purpose of the study is to substantiate the theoretical aspect of the distance model of socialization. The conducted theoretical analysis discloses the relationship between the growing popularity of virtual internet space and the emergence of new online social activities and form social interaction between individuals which proves that the internet has become a dynamic new environment of personality socialization. Based on an analysis of the theoretical provisions of socialization, the authors refine the essence of the concept of the distance socialization model. The paper gives substantiation to the provision that the distance model of socialization creates the conditions for a developing personality to express its social activity in relation to social action, inaction or social deeds through the mechanism of social expression. This distance mechanism is also present in the real social space, yet in the distance model of socialization on the web, it becomes predominantly relevant dominates and leads. The authors suggest that within the distance model of socialization, this mechanism becomes the basis for the construction of an individual’s virtual identity and its online social space as well as a foundation for the expansion of the individual's social experience in the real social space.